Chinese Classical Aesthetic in the View of Inter-Subjectivity - Haitao, Zhang (Lingua Cultura, 2008)
In contemporary China, the theory of intersubjectivity causes great significance to the construction of modern Chinese aesthetic theory but this kind of transverse dimensions of space on the outside of the transplantation of theory gave rise to some bad effects to traditional culture and classical Chinese aesthetics. Article presents a qualitative method. Its purpose to conduct research on intersubjectiveness spirit of Chinese aesthetics and literature from the dimensions of the longitudinal time. The discussion will also cause a vital significance to the building of contemporary Chinese aesthetics in this direction.